ENTREPRENEURIAL STRATEGIC INNOVATION MODEL FOR ATTAINING PREMIUM VALUE FOR THE SRI LANKAN GEM AND JEWELLERY INDUSTRY - Shyamalie Ekanayake,; Dhammika Abeysinghe, (Asian Academy of Management Journal, 2010)
Entrepreneurial innovative action is a four-pronged strategic integration; it mitigates financial risk in knowledge transfer and technology transfer, it integrates manufacturing and business strategy, and it provides policy remedy to transform the assets and capabilities of the value system. The innovation process utilises market innovations to establish a competitive advantage, gathers intellectual assets, attains proprietary rights and fosters the ability to implement appropriate strategies and sustain a competitive advantage, thus generating premium value. The entrepreneur's commitment uncovers market opportunities and exploits the inventiveness of value-system technologies to result in market innovation. The integration of the above-mentioned four forces with changing market needs transforms the capabilities of the value system to allow it to sustain business value regeneration and thus generate premium value. The failure of either one or all four forces of entrepreneurs' innovative strategies will lead to a reduction in the market value of the products and disintegrate the industry value system. This phenomena was observed in the gem and jewellery industry in Sri Lanka, where the industry has been capable enough to develop a competitive product base but has been positioned to experience a reduction in market value. This reduction has resulted in the disintegration of the industry value system, forcing firms to work in isolation.